Electro-Fenton technology for wastewater treatment: A bibliometric analysis of current research trends, future perspectives and energy consumption analysis. (April 2021) - Ismail, Saiyidah Anisah; Ang, Wei Lun; Mohammad, Abdul Wahab
Graphical abstract: Highlights: EF research trend systematically reviewed through bibliometric analysis. Characterisation of EF articles' nature of study for research progress review. Factors influencing energy consumption of various EF processes is discussed. Future perspectives on EF study are proposed. Abstract: Acceleration in global industrialisation has led to increasing release of various emerging, highly toxic refractory organic pollutants in water bodies. These contaminants have been very concerning due to their detrimental impacts on human beings as well as aquatic life even at low concentrations. Conventional wastewater treatment technology has proven to be ineffective in eliminating these pollutants, hence creating substantial attention for a more advanced Electro-Fenton (EF) technology. A systematic bibliometric analysis has been carried out based on Scopus database to comprehend the extensive research development of EF technology for the past 2 decades (2000–2019). Several aspects were analysed, namely general growth trend, journal, country, institutional, authorship and keywords analysis. VOSViewer was utilised to present a clear collaboration between authors, countries and co-occurrences between research keywords. Exponentially high publication growth was observed during the recent decade (2010–2019) highlighting the main EF research areas such as electrode and catalyst synthesis, application, mathematical modelling, technology integration and process comparison. Energy consumption analysis reveals the substantial impact of various EF operational and design parameters on the energy consumed by EF system, which then significantly define its economic viability. Future research prospects are suggested to encourage continuous development of technical, environmental and economically feasible EF system.